2014
DOI: 10.1016/j.molimm.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Human cathelicidin LL-37-derived peptide IG-19 confers protection in a murine model of collagen-induced arthritis

Abstract: Current therapies for autoimmune chronic inflammatory diseases e.g. rheumatoid arthritis (RA) include inhibitors of inflammatory cytokines. However, these therapies can result in increased risk of infections. There is a need to explore alternate strategies that can control inflammation without compromising the innate ability to resolve infections. In this study, we examined the effect of small peptides derived from endogenous cathelicidin peptides in a murine model of collagen-induced arthritis (CIA). Cathelic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 51 publications
9
44
1
Order By: Relevance
“…In agreement with these findings, others have demonstrated that a bovine cathelicidin-derived peptide, IDR1018, can aid in wound healing in S. aureus-infected murine wounds (48). In addition, another LL-37-derived synthetic peptide, named IG-19, decreased disease severity and significantly reduced the serum levels of antibodies against collagen type II in a collagen-induced arthritis model (49). Besides allowing for an assessment of the antibacterial activities of peptides on infected tissues, the advantage of using an in vitro infection model that mimics the human skin is that the possible effects of the peptides on inflammation (as exemplified by IL-8 release), cell viability, and wound healing can be monitored in the same model.…”
Section: Discussionsupporting
confidence: 55%
“…In agreement with these findings, others have demonstrated that a bovine cathelicidin-derived peptide, IDR1018, can aid in wound healing in S. aureus-infected murine wounds (48). In addition, another LL-37-derived synthetic peptide, named IG-19, decreased disease severity and significantly reduced the serum levels of antibodies against collagen type II in a collagen-induced arthritis model (49). Besides allowing for an assessment of the antibacterial activities of peptides on infected tissues, the advantage of using an in vitro infection model that mimics the human skin is that the possible effects of the peptides on inflammation (as exemplified by IL-8 release), cell viability, and wound healing can be monitored in the same model.…”
Section: Discussionsupporting
confidence: 55%
“…Very recent studies report the antibacterial peptide cathelicidin LL-37 and its fragments as a promising antifungal drug (38,39). Once secreted at the site of candidal infection, LL-37 may be actively localized on the Candida cell wall (40), thereby reducing cell wall thickness and affecting the functionality of the cytoplasmic membrane (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both pro-and antiinflammatory functions have been assigned to LL-37 and this may be modulated by the microenvironment and disease background. Anti-inflammatory actions have been reported in arthritic animal models, where a synthetically derived LL-37 peptide suppressed pro-inflammatory cytokine levels (Chow et al, 2014). LL-37 attenuates LPS-stimulated IL-6 and MCP-1 expression in periodontal ligament cells (Jonsson and Nilsson, 2012) and LPSstimulated IL-8 production in monocytes (Scott et al, 2011).…”
Section: Discussionmentioning
confidence: 99%